The relationship between the cross-sectional area of the vastus medialis oblique muscle and the anterior cruciate ligament return to sport index with the lateral step down test and the knee injury and osteoarthritis outcome score questionnaire in post–anterior cruciate ligament reconstruction patients - Intara Putri, Pande Putu Prami; Winaya, I Made Niko (Kinetic and Physiotherapy Comprehensive, 2025)
Background: Anterior cruciate ligament (ACL) reconstruction is a surgical procedure performed to repair a torn ACL. This procedure may lead to atrophy of the cross-sectional area (CSA) of the vastus medialis oblique (VMO), which could potentially impact the patient’s psychological condition. This study aimed to examine the relationship between the cross-sectional area of the VMO and ACL-RSI with the lateral step down test and KOOS questionnaire in post-ACL reconstruction patients. Methods: This study is a literature review that analyzes previous research articles as secondary data sources. The literature search was conducted using the PEO framework: Patient (P) = post-ACL reconstruction patients, exposure (E) = cross-sectional area of the vastus medialis oblique, outcome (O) = lateral step down test and KOOS. The keywords used were: “cross-sectional area of vastus medialis oblique,” “anterior cruciate ligament return to sport injury,” “lateral step down test,” “knee injury and osteoarthritis outcome score questionnaire,” and “anterior cruciate ligament reconstruction,” selected based on their relevance to the study topic. Results: Patients who had undergone ACL reconstruction showed no significant relationship between VMO CSA and KOOS scores (p > 0.05). However, there was a significant relationship between ACL-RSI scores and KOOS subscales of quality of life and sports and recreation (p < 0.05). No studies were found that directly examined the relationship between the lateral step down and either VMO CSA or ACL-RSI. Conclusion: There was a significant relationship between psychological readiness (ACL-RSI) and perceived knee function (KOOS). However, no significant association was found between muscle morphology (VMO CSA) and KOOS. Furthermore, no direct evidence currently links either VMO CSA or ACL-RSI to lateral step down test performance in patients following ACL reconstruction.